Effectiveness of Health Promotion Strategies on Malaria Preventive Behaviors in Woyla Public Health Centers (Puskesmas) - Maiza Duana; Dian Fera; Danvil Nabela; Tri Mulyono Herlambang; Anasril Anasril (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
Malaria is an infectious disease caused by intracellular obligate protozoa of the genus Plasmodium. The disease is naturally transmitted through the bite of a female Anopheles mosquito. West Aceh Regency Is a district with a high incidence of malaria. West Aceh regency ranks second only to Aceh Jaya in terms of the number of malaria sufferers. West Aceh district is also not included in the 14 districts that have been certified for malaria elimination in Aceh Province in 2016. The purpose of this study is to evaluate the effectiveness of health promotion strategies against changes in people's behaviour in preventing malaria in the East Woyla Subdistrict. This type of research is an experimental study with participatory action research (PAR) design, which is a process where researchers and participants systematically dig and solve problems. The population in this study were all community leaders, health workers, health cadres, and the entire community in East Woyla Subdistrict. A sample of 44 people. The sampling method in this study uses a random sampling quota method. Samples will represent each village in East Woyla Sub-district according to the proportion of the population in each village. The results showed that the Health Promotion strategy effectively changed people's behaviour in malaria prevention efforts. The statistical test results showed the value of Z-score = 5,781 (Z-score > 1.96), and p-value = 0.000 (p<0.05). So it can be decided that the community's health promotion strategy is effective against malaria prevention behaviour. It is recommended that the East Woyla Health Center implement a comprehensive and continuous health promotion strategy for the common goal of achieving malaria elimination in its working area of public health.